Evaluation of Phytosterols as an Alternative to Cholesterol in Practical Diets on Growth and Nonspecific Immunity of Litopenaeus vannamei - Yongkang Chen; Zhongchao Pan; Xiaoyue Li; Xinzhou Yao; Guilun He; Shiwei Xie (Aquaculture Nutrition)
This study is aimed at evaluating the effectiveness of phytosterols as an alternative to cholesterol in practical diets of Pacific white shrimp Litopenaeus vannamei from the perspective of growth and nonspecific immunity. Five diets were formulated to contain different sterol sources and levels. Two diets were supplemented with 1 g/kg cholesterol (LC (low cholesterol)) or phytosterol (LP (low phytosterol)). Other three experimental diets were supplemented with 2 g/kg cholesterol (HC (high cholesterol)), 2 g/kg phytosterol (HP (high phytosterol)), or mixed sterol source (CP, 1 g/kg cholesterol+1 g/kg phytosterol), respectively. A total of 750 healthy and uniform-sized shrimp (0.52±0.008 g) were randomly distributed into 5 groups with 3 replicates and fed with the five experimental diets for 60 days. Results showed that the growth performance of shrimp was influenced by the sterol levels and supplementation with 2 g/kg sterol level facilitated the growth of shrimp. The inclusion of phytosterol has a cholesterol-lowering effect on shrimp, as evidenced by a reduction in hemolymph cholesterol and triglyceride contents in the HP group. Besides, supplementation with 2 g/kg phytosterol or mixed sterol sources had positive effects on the hemolymph superoxide dismutase, phenol oxidase, and lysozyme as well as hepatopancreas alkaline phosphatase activities, demonstrating that the nonspecific immunity and antioxidative capacity were improved. In conclusion, phytosterols could be an appropriate alternative to partially replace dietary cholesterol in shrimp feeds. This study preliminarily revealed the effects of different sterol sources and levels on the growth and nonspecific immunity of shrimp and provided a basis for further exploration of the mechanism of phytosterol.